Effect of Negative Customer Experience and Negative Confirmation on Electronic - Word of Mouth : A Case of Food Delivery Apps in India - Sharma, Pardeep Bawa; Pathak, Rasna; Ahuja, Diksha (Indian Journal of Marketing, 2023)
Purpose : The present study explored a broad customer experience-disconfirmation-engagement framework by testing the effect of negative customer experience and negative confirmation on electronic word of mouth using customer engagement. The fact that negatively valenced customer engagement was seldom tested in such frameworks induced us to explore its effects. Methodology : Data were collected from 329 respondents against â€œnegative customer experience,â€ â€œnegative confirmation,â€ â€œnegative customer engagement,â€ and â€œnegative electronic word of mouth.â€ A two-step methodology was used wherein the measurement model was evaluated with the help of confirmatory factor analysis (CFA). After that, the proposed model was tested using structural equation modeling (SEM) using IBM SPSS AMOS 22.0. Bootstrapping was used to test the mediation effect. Findings : We found that negative customer experience and disconfirmation significantly affected negative customer engagement, which in turn significantly affected electronic word of mouth. The results also showed that negative customer engagement mediated between both negative disconfirmation and electronic word of mouth and negative customer experience and electronic word of mouth. Practical Implications : It was recommended that service managers should fill voids that pertain to the link between negative customer engagement and what may come thereafter. It would reduce the number of brand switchovers and lessen the dilution of service value. Originality : It investigated how negative customer engagement occurs in online service relationships, a construct that has never been employed in the customer confirmationâ€“customer experienceâ€“word-of-mouth paradigm.